Гарантії належного кваліфікаційного рівня судді: Європейський досвід та його імплементація у законодавство України - Мельник, Микола Григорович; Мельник, Николай Григорьевич; Mel'nik, Nikolaj (My University, 2012)
The article is devoted to defining of due judge qualification rate guarantees taking into account European experience of such guarantees formation and functioning. The guarantees are: judge professional training, organization of training. Necessary of formation of requirements to instructors which realize training of judges is grounded.
Мельник М. Г. Гарантії належного кваліфікаційного рівня судді: Європейський досвід та його імплементація у законодавство України / М. Г. Мельник // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 78-84.
Keywords: гарантії; належний кваліфікаційний рівень; суддя; європейський досвід; імплементація; професійна підготовка; організація; гарантии; надлежащий профессиональный уровень; судья; европейский опыт; имплементация; профессиональная подготовка; организация; guarantees; due qualification rate; judge; European experience; implementation; professional training; organization